Large Osteochondroma of the Scapula in a 2-Year-Old - Graeme Matthewson; Mandip Singh; Susan Thompson (Elsevier, 2019)
Osteochondromas are a common tumour comprising up to 40% of benign bone tumours. Malignant transformation of osteochondromas is quite rare but increases based on genetics (EXT gene mutation) as well as location (pelvis and scapula). Osteochondromas of the scapula generally present once they reach a size that disrupts scapulothoracic motion or is noticed as an obvious palpable mass around the scapula. Here we present a case report of a 2-year-old boy with a large circumferential osteochondroma of the right scapula. Due to the size, location and rapid expansion of the mass, concerns for malignancy were quite high. On MRI examination, T2 imaging revealed an unimpressive cartilage cap but with substantial destruction of bone and mass effect causing alteration of the architecture of the surrounding ribs. On surgical excision of the lesion, the neurovascular bundle was found to be anterior to the mass and a small, thin, misshapen scapula was left following excision. Concerning features for malignant transformation include rapid expansion, growth after skeletal maturity as well as a cartilage cap >2 cm in size. Pathologic specimen was sent, ensuring the inclusion of a portion of the underlying scapula for assessment. Results of pathology revealed a benign lesion without signs of atypia in the lesion or scapular specimen sent.Osteochondromas of the scapula should be followed closely for many reasons. First there is an increased risk of malignancy in these lesions, particularly in a large, rapidly expanding lesion. Secondly, due to the location of the lesion, consequences of mass effect are more substantial due to disruption of scapulothoracic rhythm and the potential for joint injury distal to the scapula. Third, because of its hidden nature, ventral lesions may go unnoticed, and any abnormality of scapular positioning or movement should prompt further investigation of the architecture of the scapula.